Carbon-free dry reforming of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh; Joshi, Upendra A. (Catalysis Letters, 2005)
CoNdOx (Co/Nd = 1) is a highly promising catalyst for the carbon-free CO2 reforming of methane. Influence of the Co/Nd ratio on the catalyst performance in the CO2 reforming and also on the crystalline phases and reduction by temperature programmed reduction (TPR) of the CoNdOx catalyst has also been investigated. The CoNdOx (CoNd = 1.0) catalyst consisted of mainly NdCoO3 perovskite- type mixed metal oxide and it showed not only a high resistance to carbon formation at different process conditions ( viz. temperature = 750 - 900 degrees C and gas hourly space velocity (GHSV) = 10000 - 50000 cm(3) g(-1) h(-1)) but also high activity and selectivity in the CO2 reforming process. The high resistance to carbon formation for this catalyst is attributed mostly to strong metal (Co degrees) - support (Nd2O3) interactions.
Keywords: CO2 reforming of methane to syngas; CoNdOx catalyst; NdCoO3 perovskite; resistance to carbon formation in CO2 reforming

CO2 reforming of methane combined with steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal-oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C. (Applied Energy, 2006)
CO2 reforming with simultaneous steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst (prereduced by H-2) at different process conditions has been investigated. In the simultaneous CO2 and steam reforming, the conversion of methane and H2O and also the H-2/CO product ratio are strongly influenced by the CO2/H2O feed-ratio. In the simultaneous CO2 reforming and partial oxidation of methane, the conversion of methane and CO2, H-2 selectivity and the net heat of reaction are strongly influenced by the process parameters (viz. temperature, space velocity and relative concentration of O-2 in the feed). In both cases, no carbon deposition on the catalyst was observed. The reduced NdCoO3 perovskite-type mixed-oxide catalyst (Co dispersed on Nd2O3) is a highly promising catalyst for carbon-free CO2 reforming combined with steam reforming or partial oxidation of methane to syngas. (c) 2005 Published by Elsevier Ltd.
Keywords: Co/Nd2O3 catalyst; methane; NdCoO3 perovskite-type mixed metal-oxide catalyst; Oxy-CO2 reforming of methane; simultaneous CO2 and steam reforming of methane

CO2 reforming of methane to syngas over CoOx/MgO supported on low surface area macroporous catalyst carrier: Influence of Co loading and process conditions - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Industrial & Engineering Chemistry Research, 2006)
The effect of Co loading (5-30 wt %) and process parameters ( reduction pretreatment, reaction temperature, and space velocity) have been investigated over CoOx/MgO(5%)/SA-5205 catalyst for the CO2 methane reforming process. The Co loading had a profound effect on the methane conversion and the hydrogen selectivity ( initial and time-on-stream activity) for the unreduced catalysts. While negligible methane conversion was observed for the 5 and 10 wt % Co loading catalyst, methane conversions > 95% were obtained over the high Co loading ( 20 and 30 wt %) catalysts; hydrogen selectivity followed the same trend as methane conversion. The Co loading level had a relatively smaller influence in the case of the reduced catalysts. While the 5 wt % Co catalyst showed low methane conversion activity (< 30%), the 10 wt % Co catalyst showed methane conversion levels comparable to those of the high Co loading catalysts. The high Co loading catalysts showed an excellent time-on-stream performance for the CO2 methane reforming reaction. X-ray diffraction and temperature-programmed reduction experiments indicate that the interesting activity behavior exhibited by the catalysts is related to the different phases ( and their reducibility) present in the catalysts at different Co loadings. The hydrogen selectivity was found to decrease with decreasing reaction temperature and increasing space velocity due to the increased simultaneous occurrence of the reverse water-gas shift reaction along with the CO2 reforming reaction.

CO2 reforming of methane to syngas over highly active and stable supported CoOx (accompanied with MgO, ZrO2 or CeO2) catalysts - Mondal, Kartick C.; Choudhary, Vasant R.; Joshi, Upendra A. (Applied Catalysis A-General, 2007)
{Catalytically inactive CoOx-MgO (calcined at 900 degrees C) becomes highly active and selective in the CO2 reforming of methane to syngas when it is deposited on a commercial low surface-area macro-porous silica-alumina support (SA-5205) or when CoOx is deposited on the support precoated with MgO. Both the supported CoOx and MgO containing catalysts (CoOx -MgO/SA-5205 and CoOx/MgO/SA-5205) show high methane conversion (> 98%) activity and H-2 selectivity (> 94%) and also high stability against carbon deposition [
Keywords: arylboronic acids; diarylmethylidenefluorene; dibromomethylidenefluorene; Pd-mediated coupling; Suzuki reaction